2018
DOI: 10.1590/s1677-5538.ibju.2017.0431
|View full text |Cite
|
Sign up to set email alerts
|

Endourologic strategies for a minimally invasive management of urinary tract stones in patients with urinary diversion

Abstract: ObjectiveTo present our experience in minimally invasive management of urinary tract stones in patients with urinary diversion.Materials and MethodsWe retrospectively reviewed 26 patients with urinary tract stones after cystectomy and urinary diversion. The types of urinary diversion were ileal conduit, colon conduit, ileal orthotopic neobladder in 19, 4, and 3 patients, respectively. At postoperative days 2, a plain KUB and urinary ultrasonography were performed in order to assess stone fragmentation or hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…We appreciated the valuable comments on our recent published article in the International Braz J Urol ( 1 , 2 ). We agree with the commentary, to our knowledge, these studies have shown that the complicated patients with lower tract stone were treated by endoscopic management.…”
mentioning
confidence: 97%
“…We appreciated the valuable comments on our recent published article in the International Braz J Urol ( 1 , 2 ). We agree with the commentary, to our knowledge, these studies have shown that the complicated patients with lower tract stone were treated by endoscopic management.…”
mentioning
confidence: 97%
“…We read with interest the recent paper by Zhong et al examining the variety of endourological strategies available for the management of urinary tract stone disease in patients following urinary diversion ( 1 ).…”
mentioning
confidence: 99%
“…The authors report a retrospective study involving 26 patients who underwent urinary diversion and who subsequently presented with stone related problems and allude to the variety of techniques available ( 1 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations